Reconstructing an Islamic Education Curriculum Based on Islamic Values for Strengthening Educational Ethics: An Implementational Case Study in Madrasah - Siti Saroh Hasibuan; Sri Wahyuni; Lilis Gusliyah; Nanda Mulyani Pratiwi; Ana Susiana; Abdul Hadi Alghani (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2026)
ENGLISH: Reconstructing an Islamic Education Curriculum Based on Islamic Values for Strengthening Educational Ethics: An Implementational Case Study in MadrasahObjective: This study aims to analyze the reconstruction of an Islamic Education curriculum based on Islamic values to strengthen educational ethics in madrasahs through an examination of its planning, implementation, evaluation, and impact on student character development. Method: A qualitative approach with a case study design was employed. Data were collected through observations, semi-structured interviews, and document analysis, and were subsequently analyzed using the Miles, Huberman, and Saldaña interactive model with triangulation. Results: Curriculum reconstruction systematically integrated Islamic values into learning objectives, content, instructional strategies, assessment, and school culture, thereby enhancing students' discipline, honesty, responsibility, and social awareness, as well as advancing teachers' professionalism. Conclusion: Educational ethics are strengthened through the integration of curriculum, pedagogy, leadership, and school culture within a unified educational ecosystem. Contribution: This study proposes a systematic framework for implementing an Islamic value-based curriculum that supports sustainable character development in madrasahs.INDONESIA: Rekonstruksi Kurikulum Pendidikan Islam Berbasis Nilai-Nilai Keislaman dalam Penguatan Etika Pendidikan: Studi Kasus Implementatif di MadrasahTujuan: Penelitian ini bertujuan untuk menganalisis rekonstruksi kurikulum Pendidikan Islam berbasis nilai-nilai keislaman dalam memperkuat etika pendidikan di madrasah melalui kajian terhadap perencanaan, implementasi, evaluasi, dan dampaknya terhadap pembentukan karakter siswa. Metode: Menggunakan pendekatan kualitatif dengan desain studi kasus. Data dikumpulkan melalui observasi, wawancara semi-terstruktur, dan studi dokumentasi, analisis menggunakan model interaktif Miles, Huberman, dan Saldaña dengan triangulasi. Hasil: Rekonstruksi kurikulum mengintegrasikan nilai-nilai Islam secara sistematis ke dalam tujuan pembelajaran, materi, strategi pembelajaran, penilaian, dan budaya madrasah sehingga meningkatkan kedisiplinan, kejujuran, tanggung jawab, dan kepedulian sosial peserta didik, serta profesionalisme guru. Kesimpulan: Penguatan etika pendidikan dicapai melalui integrasi kurikulum, pembelajaran, kepemimpinan, dan budaya madrasah dalam suatu ekosistem pendidikan yang terpadu. Kontribusi: Penelitian ini menawarkan kerangka implementatif kurikulum berbasis nilai-nilai Islam yang sistematis untuk mendukung pengembangan karakter secara berkelanjutan di madrasah.